(untitled) (Revista INTEREDU11, 2021)
This essay’s subject of interest is developed from the construction of psychopedagogy in epistemological and scientific terms. This matter has become the self-construction of this science and based on the permanent linkage of knowledge from other disciplines and sciences. It is then articulated a new understanding at epistemolygic level whose boundaries intersect in the context of complexity –such as science and cognitive style– that not only addresses the problems associated with school learning, but also covers the problematization of human learning in various dimensions and scenarios. It is concluded that there is a scenario associated with the sciences of complexity in which psychopedagogy assumes a convening and interdisciplinary character that allows it to delv into the formulation of problems based on the ability to interact with other scientific territories, and thus build one of its own.